Berengario da Carpi and the Renaissance of Brain Anatomy - Parent, André (Frontiers in Neuroanatomy, 2019)
Berengario da Carpi (Jacopo Barigazzi) was born around 1460 in the small Italian town of Carpi near Modena. Berengario’s father, Faustino, was a reputable barber-surgeon who initiated his son early into the art of anatomy and surgery. After his graduation from the University of Bologna in 1489, Berengario rapidly acquired an enviable reputation as a physician and surgeon following the successful treatment of several dignitaries, including Lorenzo de’ Medici, Duke of Urbino who suffered a severe head injury in 1517. While professor of anatomy and surgery at the University of Bologna, Berengario published in 1518 his De fractura cranei, a landmark work on cranio-cerebral surgery. Berengario’s masterpiece, however, is undoubtedly his detailed Commentaria on the famous medieval anatomy treatise of Mondino de’ Liuzzi (ca. 1270–1326) that he published in 1521. A shorter version entitled Isagogae Breves appeared a year later. Besides a facsimile of Mondino’s work, Berengario’s Commentaria contains a wealth of new information, including observations that challenged Galenic physiology. Galen taught that the rete mirabile—a vascular plexus believed to occur at the basis of the human brain—is the locus where the vital spirit is transformed into the more sophisticated animal spirit that is stored in the brain ventricles to be later released at the periphery through a journey within hollow nerves. Courageously, Berengario wrote that despite many attempts he was unable to detect the famous rete mirabile in humans. He also noted that the nerves linked to the brain are solid structures, not hollow tubes, as advocated by Galen. His conclusions were based on a systematic dissection method that he called anatomia sensibilis, a term that emphasizes the sensory over textual versions of the truth. Berengario contributed significantly to human brain anatomy, with a detailed description of the meninges and cranial nerves and the first comprehensive view of the ventricular system, including choroid plexuses, interventricular foramen, infundibulum, pituitary stalk and gland. Berengario, who died around 1530 in Ferrara, should be remembered for his catalyzing role in the transmutation of medieval morphological knowledge into a modern anatomical science based upon direct observation and experimental demonstration.